A2_6 Computational railgun dynamics & back EMF - Hands, Thomas; Marshall, David; Griffiths, Ian; Douglas, Gary (Physics Special Topics, 2011)
Railguns are projectile firing devices that operate on the basic principles of electro-magnetism. In thisÂ paper we describe a novel method of simulating the dynamics of such a gun by solving a system ofÂ differential equations numerically. We then use this method to explore the effect of back EMF on railgunÂ dynamics.